No interior da medida: punição e relações raciais no sistema socioeducativo na cidade de São Carlos - Mattos, Kênia Rodrigues (Universidade Federal de São Carlos, 2023)
This dissertation investigated how ethnic-racial relations are evident in the implementation of socio-educational measures applied in an open environment (assisted liberty and provision of services to the community) and closed environments (hospitalization) in the municipality of São Carlos. The methodology chosen for the investigation was mixed, being of a qualitative nature, with analysis of the guiding and official documents on the theme of the centers implementing socio-educational measures and interviews (in-depth with a semi structured script), carried out with employees of the socio-educational system. The quantitative methodology refers to the analysis of sociodemographic data from the municipality's juvenile justice system. The aim, therefore, was to observe the differences in execution and compliance with measures in the two institutions that carry out measures in an open and closed environment (Salesianos and Fundação Casa). In the qualitative research findings, the hypothesis that differences exist was confirmed, with indications that in the closed environment, where subjection is more present, racial issues are less demanded, at the same time, in both institutions the pedagogical commitment to the ethnic-racial relations is not mobilized by the teams. In quantitative data, racial disparities were observed in the juvenile justice system. The results presented here may contribute to themes explored in areas of Sociology such as violence, deprivation of liberty, juvenile justice and race relations
Inside the measure: punishment and racial relations in the socio-educational system in the city of São Carlos
Keywords: Relações raciais; Medidas socioeducativas (MSE); Adolescência a quem se atribui a prática de ato infracional; São Carlos; Race relations; Socio-educational measures (MSE); Adolescence attributed to the commission of an infraction; CIENCIAS HUMANAS::SOCIOLOGIA